Pertanggungjawaban Hukum atas Penembakan Tenaga Medis Perawat Razan Al Najjar dalam Konflik Perbatasan Gaza: Perspektif Hukum Humaniter Internasional - Ghaizka Figo Alfaeza; Desyana Aqirtasari; Nayla Widya Agustin; Dataran Tinggi Golan; Abdullah Dafiq Shalih Azzam; Muhammad Andi Saputro (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
The shooting of Palestinian medical volunteer Razan Al-Najjar on June 1, 2018 in Khan Younis, Gaza Strip, by Israeli forces constitutes a serious allegation of violation of International Humanitarian Law (IHL). This research explicitly aims to examine (i) the legal status and scope of protection afforded to medical personnel under IHL, and (ii) the forms of legal accountability applicable to the shooting of Razan Al-Najjar through a case-based normative legal analysis grounded in treaty law and authoritative interpretations. Using a normative juridical method with statute, conceptual, and case approaches, this study analyzes the 1949 Geneva Conventions, the 1977 Additional Protocols, the Rome Statute, and relevant UN fact-finding reports. The study finds that the incident reflects a systemic breach of the IHL principles of distinction and special protection of medical personnel, corroborated by recurring patterns of attacks against health workers in Gaza. The novelty of this research lies in identifying the shooting as a legally cognizable form of individual criminal responsibility for war crimes specifically willful killing and intentionally targeting medical personnel as well as exploring the dual-layer accountability involving state responsibility and command responsibility. Furthermore, instead of framing “sanctions” simplistically, this research clarifies that enforcement may occur through mechanisms of international accountability, including referrals to the International Criminal Court, targeted measures under UN mechanisms, and obligations of third states to ensure respect for IHL under Common Article 1 of the Geneva Conventions. This study concludes that the shooting of Razan Al-Najjar meets the legal threshold of an IHL violation with potential war crime implications, and emphasizes the urgent need to strengthen international enforcement pathways to address persistent impunity in attacks on medical personnel